High Efficiency, Low Cost 3" Diameter Silicon Solar Cells - Kukulka, Jerry P. (My University, 1978)
Silicon solar cells were produced using inexpensive techniques for obtaining high efficiencies. Large area cells were made with efficiencies greater than 10% (AM1) which were subsequently mounted on a Solar panel for future evaluation.
Keywords: silicon solar cells; solar panel; high efficiency; 3" diameter